The Role of gsp Mutations on the Development of Adrenocortical Tumors and Adrenal Hyperplasia - Villares Fragoso, Maria Candida Barisson; Wanichi, Ingrid Quevedo; Cavalcante, Isadora Pontes; Mariani, Beatriz Marinho de Paula (Frontiers in Endocrinology, 2016)
Somatic GNAS point mutations, commonly known as gsp mutations, are involved in the pathogenesis of McCune–Albright syndrome (MAS) and have also been described in autonomous hormone-producing tumors, such as somatotropinoma, corticotrophoma, thyroid cancer, ovarian and testicular Leydig cell tumors, and primary macronodular adrenocortical hyperplasia (PMAH) (1–3). The involvement of gsp mutations in adrenal tumors was first described by Lyons et al. Since then, several studies have detected the presence of gsp mutations in adrenal tumors, but none of them could explain its presence along or the mechanism that leads to tumor formation and hormone hypersecretion. As a result, the molecular pathogenesis of the majority of sporadic adrenocortical tumors remains unclear (3). PMAH has also been reported with gsp somatic mutations in a few cases. Fragoso et al. identified two distinct gsp somatic mutations affecting arginine residues on codon 201 of GNAS in a few patients with PMAH who lacked any features or manifestations of MAS. Followed by this discovery, other studies have continued looking for gsp mutations based on strong prior evidence demonstrating that increased cAMP signaling is sufficient for cell proliferation and cortisol production (2, 4). With consideration for the previously reported findings, we conjecture that although somatic activating mutations in GNAS are a rare molecular event, these mutations could probably be sufficient to induce the development of macronodule hyperplasia and variable cortisol secretion. In this manuscript, we revised the presence of gsp mutations associated with adrenal cortical tumors and hyperplasia.